Essays on vertical price restraint, merger and competitive conduct - Faheem, Adeel (Kansas State University, 2019)
The dissertation investigates the two-fold impact on the competitive conduct of U.S. brewers of a) changes in the legal approach towards vertical price restraint and b) recent mergers and acquisition activities of leading brewers. These changes may have profound repercussions for the level of competition in the highly concentrated US beer industry. The first essay analyzes the impact of change in legal environment toward vertical price restraint on the competitive behavior of brewers in the US beer industry. Resale price maintenance (RPM) is the practice whereby upstream firms in an industry, e.g. manufacturers, make an agreement with downstream firms, e.g. retailers, that the downstream firms will sell the manufacturer's product at certain prices. The 2007 US Supreme Court’s decision in the Leegin case resulted in a legal paradigm shift in which the legality of a given RPM agreement is based on a “rule of reason” approach instead of being “per se illegal”, i.e. the new approach calls for a ruling on the legality of an agreement in question based on weighing benefits and harms. This essay provides evidence on whether market data outcomes in the US beer industry are consistent with the use of RPM prior to and subsequent to the Leegin decision, and if so, whether RPM equilibrium outcomes are on net anticompetitive. We find that vertical relationships between brewers and retailers are best approximated by brewers using nonlinear, instead of linear, wholesale price contracts when selling to retailers, and brewers using RPM with retailers during post-Leegin periods but no RPM during pre-Leegin periods. Furthermore, our findings do not support that RPM agreements are on net anticompetitive in the US beer market. The second essay explores the impact of the recent merger in the US beer industry. Using structural econometric models of demand and supply, this essay analyzes competitive conduct of national brewers in the US beer market. The analysis focuses on the recent merger between ABI and SABMiller in the US beer industry. We model supply behavior of ABI and MillerCoors by specifying a parameter measuring the extent to which these brewers internalize price externalities. Contrary to past findings, our empirical analysis reveals that the leading domestic brewers’ price setting behavior is best approximated by Bertrand Nash model in the both pre-merger and post-merger periods.
Keywords: Vertical contracting; Beer Industry; Mergers